PPARG in osteocytes controls cell bioenergetics and systemic energy metabolism independently of sclerostin levels in circulation - Sudipta Baroi; Piotr J. Czernik; Mohd Parvez Khan; Joshua Letson; Emily Crowe; Amit Chougule; Patrick R. Griffin; Clifford J. Rosen; Beata Lecka-Czernik (Elsevier, 2024)
Objective: The skeleton is one of the largest organs in the body, wherein metabolism is integrated with systemic energy metabolism. However, the bioenergetic programming of osteocytes, the most abundant bone cells coordinating bone metabolism, is not well defined. Here, using a mouse model with partial penetration of an osteocyte-specific PPARG deletion, we demonstrate that PPARG controls osteocyte bioenergetics and their contribution to systemic energy metabolism independently of circulating sclerostin levels, which were previously correlated with metabolic status of extramedullary fat depots. Methods: In vivo and in vitro models of osteocyte-specific PPARG deletion, i.e. Dmp1CrePparγflfl male and female mice (γOTKO) and MLO-Y4 osteocyte-like cells with either siRNA-silenced or CRISPR/Cas9-edited Pparγ. As applicable, the models were analyzed for levels of energy metabolism, glucose metabolism, and metabolic profile of extramedullary adipose tissue, as well as the osteocyte transcriptome, mitochondrial function, bioenergetics, insulin signaling, and oxidative stress. Results: Circulating sclerostin levels of γOTKO male and female mice were not different from control mice. Male γOTKO mice exhibited a high energy phenotype characterized by increased respiration, heat production, locomotion and food intake. This high energy phenotype in males did not correlate with "beiging" of peripheral adipose depots. However, both sexes showed a trend for reduced fat mass and apparent insulin resistance without changes in glucose tolerance, which correlated with decreased osteocytic responsiveness to insulin measured by AKT activation. The transcriptome of osteocytes isolated from γOTKO males suggested profound changes in cellular metabolism, fuel transport, mitochondria dysfunction, insulin signaling and increased oxidative stress. In MLO-Y4 osteocytes, PPARG deficiency correlated with highly active mitochondria, increased ATP production, and accumulation of reactive oxygen species (ROS). Conclusions: PPARG in male osteocytes acts as a molecular break on mitochondrial function, and protection against oxidative stress and ROS accumulation. It also regulates osteocyte insulin signaling and fuel usage to produce energy. These data provide insight into the connection between osteocyte bioenergetics and their sex-specific contribution to the balance of systemic energy metabolism. These findings support the concept that the skeleton controls systemic energy expenditure via osteocyte metabolism.